Detection of Albumin and Urea in Kidney Failure Patients by Optical Biosensor - Alani, Marwa .S.; Al-Mayaly, Ithar Kamil (Iraqi Journal of Science, 2022)
The major function of the kidney is the filtration and secretion of the final products of metabolism and the excess of electrolytes. The term kidney failure denotes inability of the kidneys to perform excretory function leading to retention of nitrogenous waste products from the blood. Biosensor are most accurate, with a rapid diagnosis ,more costly method than the traditional method to avoid any biological changes in blood sample that lead to changes optical characteristic (refractive index and absorption) of blood sample. The current study was designed to single mode more Sensitivity than multi mode for Biomarkers were recorded for Albumin 5447.06, 5193.93 and Urea sample 2623.14, 1998.44 in sm and mm respectively .